Causes and types of injuries during ippon-seoi-nage throw - Rukasz, W.; Sterkowicz, S.; Klys, A. (Archives of Budo, 2011)
Background: The purpose of this study was to assess the kind and causes of the injury profile of senior male judoka competing at the international level during ippon-seoi-nage throw. Material and methods: Subjects consisted of 52 competitors participating in the Olympic Games, World and European Championships and Polish National Individual Judo Championships. The so-called epidemiological standardized medical history were used in this study. Simple check-off forms were used to collect the injury data, including injury type, location, and mechanism. Results: Competitors sustained 448 injuries in total. Sixty-five injuries happened during the ippon-seoi-nage throw. It was found that: mostly appeared to be sprains of the knee joint during the execution of the ippon-seoi-nage throw, 2) the most frequent cause of injuries was during sports contests, 3) injuries mostly occurred in a competitor who was attacking on ippon-seoi-nage, 4) there is a high risk of repeated injuries during the ippon-seoi-nage throw mostly caused by too quick a resumption of physical activities after the sustained trauma. Conclusions: Possible applications of this work are preventive actions against injuries. Coaches should use this more to exactly identify the mechanisms of injuries. We would like emphasize that routine post-trauma treatment and rehabilitation procedures restore judoka to fitness only to some degree. From the trainer`s perspective, it has been suggested that it is necessary and indispensable to individualize and modify the training course process of the judoka who had accidents.